2009
DOI: 10.1016/j.jcps.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Consumer decision making and aging: Current knowledge and future directions

Abstract: We review existing knowledge about older consumers and decision making. We develop a conceptual framework that incorporates the notion of fit between individual characteristics, task demands and the contextual environment. When the fit is high, older consumers use their considerable knowledge and experience to compensate for the impact of any age-related changes in abilities and resources. When the fit is relatively low, older consumers feel increased need to adapt their decision making processes. We discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
251
1
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(273 citation statements)
references
References 94 publications
(120 reference statements)
8
251
1
13
Order By: Relevance
“…A growing body of evidence suggests that age effects are most likely to emerge on deliberative-type tasks (Hanoch, Wood & Rice, 2007), especially ones that are cognitively demanding or lack a fit between the person and the decision environment (Finucane, Mertz, Slovic, & Schmidt, 2005;Yoon, Cole, & Lee, 2009). Furthermore, aging is associated with declines in fluid abilities, speed of processing, working memory, and executive functioning (Schaie & Willis, 2002).…”
Section: Age Decision Making and Strategy Selectionmentioning
confidence: 99%
“…A growing body of evidence suggests that age effects are most likely to emerge on deliberative-type tasks (Hanoch, Wood & Rice, 2007), especially ones that are cognitively demanding or lack a fit between the person and the decision environment (Finucane, Mertz, Slovic, & Schmidt, 2005;Yoon, Cole, & Lee, 2009). Furthermore, aging is associated with declines in fluid abilities, speed of processing, working memory, and executive functioning (Schaie & Willis, 2002).…”
Section: Age Decision Making and Strategy Selectionmentioning
confidence: 99%
“…Recognizing that the self-concept is dynamic over a person's lifespan, a sub-domain in this field has evolved to investigate how a person's chronological age (herein actual age) impacts his or her self-concept and, subsequently, their brand perceptions (e.g., Chaplin and John 2005;Loroz 2004;Yoon et al 2009). More than two decades ago, however, Demo (1992) indicated that the focus of self-concept related research had been too narrow (i.e., student samples of young adults), thus limiting the applicability of the outcomes to individuals in other life-stages.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, applications to consumer research focusing on the full spectrum of a consumer's selfconcept life cycle and, subsequently, its impact on brand perceptions, such as brand attitude, have been sparse. Focusing mainly on one phase of the life cycle, these studies have shown that differences in cognitive development, as well as neural structures, are responsible for variations in the decisionmaking processes pertaining to brands among children (Chaplin and John 2007) and individuals in late adulthood when compared to young adults (Yoon et al 2009). Recent work by Moschis (2012) offers a theoretically rich and broad review of consumer behavior among older consumers, including implications of the self-concept, but it does not delve into the other life-stages of a consumer's self-concept.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, older consumers have different decision-making processes (Peters, 2010;Queen, Hess, Ennis, Dowd & Grühn, 2012;Yoon, Cole, & Lee, 2009), all of which impacts their attitudes towards possessions (Ekerdt, 2009;Folkman Curasi, Price, & Arnould, 2010), and brand choice (Lambert-Pandraud & Laurent, 2010). Older and younger consumers differ in the way they make product-related decisions (Queen et al, 2012;Yoon et al, 2009) and age-related differences in advertising processing and effectiveness has been welldocumented for decades (Burnett, 1991;Cole & Balasubramanian, 1993;Johnson & Cobb-Walgren, 1994). Clearly, what works when targeting younger people will not necessarily work with older adults.…”
Section: Introductionmentioning
confidence: 99%